2019
DOI: 10.1038/s41598-019-41084-6
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose fibrils formation and organisation of cytoskeleton during encystment are essential for Acanthamoeba cyst wall architecture

Abstract: Acanthamoebae success as human pathogens is largely due to the highly resistant cysts which represent a crucial problem in treatment of Acanthamoeba infections. Hence, the study of cyst wall composition and encystment play an important role in finding new therapeutic strategies. For the first time, we detected high activity of cytoskeletal elements – microtubular networks and filamentous actin, in late phases of encystment. Cellulose fibrils – the main components of endocyst were demonstrated in inter-cystic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 73 publications
2
34
0
Order By: Relevance
“…Acanthamoeba cysts have an ectocyst wall (the outer cyst wall) consisting of acid-insoluble protein-containing materials and an endocyst wall (the inner cyst wall), which is partially composed of cellulose [3,7,8]. Recent studies have shown that cellulose fibrils exist in both cyst walls, and cellulose synthesis has been suggested as an important target for the treatment of Acanthamoeba infections [74]. Previous research on cellulose synthesis inhibitors and the knockdown of Acanthamoeba cellulose synthase has found that cellulose is essential to the formation of cyst walls during encystation [17,75].…”
Section: Discussionmentioning
confidence: 99%
“…Acanthamoeba cysts have an ectocyst wall (the outer cyst wall) consisting of acid-insoluble protein-containing materials and an endocyst wall (the inner cyst wall), which is partially composed of cellulose [3,7,8]. Recent studies have shown that cellulose fibrils exist in both cyst walls, and cellulose synthesis has been suggested as an important target for the treatment of Acanthamoeba infections [74]. Previous research on cellulose synthesis inhibitors and the knockdown of Acanthamoeba cellulose synthase has found that cellulose is essential to the formation of cyst walls during encystation [17,75].…”
Section: Discussionmentioning
confidence: 99%
“…Cyst walls are largely composed of acid-resistant proteins and polysaccharides, among which cellulose is one of the key constituents [13]. Magistrado-Coxen et al [24] demonstrated that purified cyst walls retained an outer ectocyst layer, an inner endocyst layer, and ostioles that connect them.…”
Section: Discussionmentioning
confidence: 99%
“…For cellulose, glycogen phosphorylase is the key enzyme that breaks down glycogen to provide glucose for the synthesis of cellulose [11, 12]. Garajová et al [13] detected clustering of intramembranous particles during encystation. It was suggested that during endocyst formation, intramembranous particle clusters represent cellulose microfibril terminal complexes involved in cellulose synthesis that are reduced after cyst wall completion.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we have demonstrated that in the cyst, the chitin is synthesized by membrane-bound chitin synthase enzyme. Recently, a very similar model for cellulose microfibril synthesis by membrane-bound cellulose synthase has been proposed in Achanthamoeba cyst (36). We believe both the processes are taking place simultaneously in Entamoeba.…”
Section: Localization Of the Chitin Synthase On Cyst Surface Guides Cmentioning
confidence: 99%